A cost-effectiveness analysis of intensive therapy of type 2 diabetes mellitus (results of Steno-2 study) - Yury Shavkatovich Khalimov (Endocrinology Research Centre, 2011)
Intensive combined therapy including modification of the lifestyle, intake of metformin and/or sulfonylureas, insulin treatment in the absence ofadequate HbAc1 control, hypolipidemic, early antihypertensive and antithrombotic therapy not only decreases the frequency of DM2 complicationsbut also reduces the total cost of the treatment (1.8 times compared with traditional therapy). Reduction in cardiovascular mortality achieved inSTENO-2 was due to intense control of risk factors at early stages of therapy with the use of modified release gliclazide (Diabeton MV). This treatmentis considered to be not only more efficacious than routine therapy but also to significantly reduce the cost of the management of DM2